A Typology of Street Robbery and Gang Organization: Insights from Qualitative Research in Scotland. (14th December 2018) - Harding, Simon; Deuchar, Ross; Densley, James; McLean, Robert
Abstract: Utilizing interviews with 42 current and ex-street offenders, this study explores the relationship between street gang organization and robbery. Robbery type is affected by level of organization exhibited by the gang. For recreational and territorial young street gangs, robbery is opportunistic, occurring in a diffuse manner, and conducted individually, even when others are present as 'backup'. For criminal gangs, robbery is often planned in advance with proceeds of crime divided more evenly amongst group members. Serious Organized Crime gangs are typically more specialized; thus, robbery may often be the gang's main 'occupation'. For organized crime groups, robbery most often occurs in the illegitimate market, but can be aimed at legitimate and highly profitable institutions. We make sense of these findings with reference to street capital theory and present implications for future research and practice.